Scanning Acoustic Microscopy of Annealing Effects for Aluminium Thin Film Deposited on Silicon Substrate - Chafia Atailia; Lakhdar Deboub; Amar Boudour; Youcef Boumaiza (Металлофизика и новейшие технологии, 2018)
Scanning acoustic microscope (SAM) has proved to be a powerful new technique for investigation and characterization of mechanical properties of materials, especially, the opaque ones. Non-destructive measurements can be carried out using SAM in the vicinity of materials’ surfaces or relatively deeper away from them. The present work is focussed on the effects of annealing on mechanical properties of samples composed of an Al layer (10 μμm) on Si substrate. Combining the results obtained from the so-called acoustic signature and acoustic images of the Al/Si interface with those from the lateral and longitudinal waves (Rayleigh speeds), it is possible to deduce that the best homogeneous adhesion is obtained after annealing at 500°C.